2015
DOI: 10.1002/dmrr.2664
|View full text |Cite
|
Sign up to set email alerts
|

Memory and executive functions in persons with type 2 diabetes: a meta‐analysis

Abstract: Literature suggests that persons with type 2 diabetes mellitus (T2DM) are at risk for cognitive impairment, hence dementia. Common domains reported to be affected in those with T2DM are memory and executive functions. The extent of influence of T2DM on these domains has varied among studies. A systematic review and meta-analysis was carried out to understand whether sub-domains contributed to the variations observed in published research. We searched 'PubMed', 'ScienceDirect', 'SciVerseHub', 'Psychinfo', 'Proq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 62 publications
(185 reference statements)
9
64
1
9
Order By: Relevance
“…There is thus an obvious need for more information about the possible early adverse effects of diabetes on cognitive functions. Numerous reviews and meta-analyses link type 2 diabetes to cognitive deficits and describe the multiple mechanisms underlying those deficits in older people (Awad, Gagnon, & Messier, 2004;Kodl & Seaquist, 2008;McGrimmon, Ryan, & Frier, 2012;Monette, Baird, & Jackson, 2014;Palta, Schneider, Biessels, Touradji, & Hill-Briggs, 2014;Reijmer, van den Berg, Ruis, Kappelle, & Biessels, 2010;Sadanand, Balachandar, & Bharath, 2015;Vincent & Hall, 2015). According to these studies, cognitive deficits in diabetes patients are most frequently evident in the domains of memory, executive functions and speed of information processing.…”
Section: Introductionmentioning
confidence: 99%
“…There is thus an obvious need for more information about the possible early adverse effects of diabetes on cognitive functions. Numerous reviews and meta-analyses link type 2 diabetes to cognitive deficits and describe the multiple mechanisms underlying those deficits in older people (Awad, Gagnon, & Messier, 2004;Kodl & Seaquist, 2008;McGrimmon, Ryan, & Frier, 2012;Monette, Baird, & Jackson, 2014;Palta, Schneider, Biessels, Touradji, & Hill-Briggs, 2014;Reijmer, van den Berg, Ruis, Kappelle, & Biessels, 2010;Sadanand, Balachandar, & Bharath, 2015;Vincent & Hall, 2015). According to these studies, cognitive deficits in diabetes patients are most frequently evident in the domains of memory, executive functions and speed of information processing.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Japanese patients with T2D that also employed the MoCA test to evaluate cognitive function/ domains has shown that patients with diabetes and mild cognitive impairment had lower scores for frontal lobe function (attention, language and abstraction) and delayed recall (17). Moreover, a recent systematic review and meta-analysis of 15 studies (n=23796; 2370 with T2D) has confirmed that T2D is associated with impairment in memory and executive function (18). A longitudinal study with a 12-year follow-up reported that individuals with T2D presented accelerated cognitive decline, mainly in the information-processing speed, executive function and delayed word recall compared with subjects without diabetes (19).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, factors such as long evolution of DM, elevated HbA1c levels, or history of insulin treatment are considered risk factors for the development of CIM. Previous work has demonstrated that Mexican-American participants with DM had a greater risk of dementia and CIM in comparison with non-diabetic participants [6][7][8] . Similarly, DM patients also have a higher risk of geriatric conditions, including dementia, disability, falls, and urinary incontinence 9 .…”
Section: Introductionmentioning
confidence: 97%